ANALISIS FAKTOR LINGKUNGAN INTERNAL DAN EKSTERNAL PENGEMBANGAN USAHA IKAN SIDAT (ANGUILLA SP.) DI KOTA PALU - Salanggon, Alismi M; Laapo, Alimudin; Tantu, Fadly Y (KAUDERNI : Journal of Fisheries, Marine and Aquatic Science, 2016)
This study aims to analyzed Internal Factor Evaluation, External Factor Evaluation, SWOT and Grand Strategy Matrices. The results showed that the strengths of eel business development in Palu were experience in the eel business, regular customers and suppliers as well strategic business location. The weaknesses were that the collectors/traders/middlemen don?t yet know how to grow out glass eels and captive breeding is not yet possible, business management is still family-oriented and production capacity is still limited. Opportunity factors for eel business development in Palu were high market demand (domestic and foreign), eel resources are still abundant and eel prices remain high. While threat factors were weaknesses in legislation/regulation on eels, environmentally damaging capture methods, and changes in climate that affect the availability of eels. The strategy for eel business development in Palu City was in quadrant I, which is a Strength-Opportunity (S-O) or aggressive strategy